Andreas Karayan’s pioneering, queer counter-discourse in 20th-century Cypriot art - Danos, Antonis (My University, 2024)
The pioneering depiction of male nudes by the Cypriot painter Andreas Karayan (b. 1943) caused quite a stir in the Cypriot art scene, when exhibited from the late 1970s onwards. Using Constantine Cavafy’s poetry as a starting point and recurring reference, Karayan portrays the male nudes as both sexual(ized) subjectivities, as well as, and because of their eroticism, embodiments of social protest and queer subversion. Even more subversive, however, are some other works, from the late 1970s and through the 1980s: images of (fully dressed) young men in public spaces – bus stops, streets, coffee shops – and of sailors and soldiers in seemingly banal conditions (for instance, resting before or after an official parade). Such works, for the first time in Cypriot art, not only brought, literally, into the open, (homo)erotic desire (gazes are exchanged, seeking response, or are directed toward the viewer), but they are also imbued with political irony and critique that interrogate issues, and queerly subvert discourses, of power, desire, and national and other ‘sacred’ symbols of collective identity
Keywords: gay art; Andreas Karayan; queer counter-discourse; male nude; public sphere; Cyprus